Arsenic(v) removal from aqueous solutions using ferromagnetic activated carbon: equilibrium and kinetic studies - Sanou, Yacouba; Phuong, Nguyen; Pare, Samuel; Phuoc, Nguyen (Revue des sciences de l’eau / Journal of Water Science)

(untitled) (Université du Québec - INRS-Eau, Terre et Environnement (INRS-ETE), 2019)
Arsenic pollution is one of the global issues which affect the drinking water supply in Burkina Faso, mainly in rural areas. To mitigate this water pollution, ferromagnetic activated carbon (FAC) has been prepared by chemical activation using rice husk and iron chloride solution to be used as an adsorbent of arsenic. Characterization with some analytical techniques revealed this carbon is microporous with a specific surface area of 150 m2∙g-1 and ferromagnetic properties. This work aims to evaluate the equilibrium conditions of As(V) removal and the adsorption capacity of FAC. Batch experiments were undertaken to evaluate the performance of FAC for arsenic removal under various operating conditions and the mechanism of the removal process. Results showed an increase of the removal percentage with the increase of the contact time, indicating a saturation during 60 min. The removal of As(V) is influenced by the increase of the initial arsenic concentration causing an increase of the adsorption capacity of FAC. The increase of pH showed a variation of the removal percentage indicating a maximum removal at pH 7 which corresponds to an adsorption capacity of 153 µg∙g-1. Both monolayer adsorption and ion exchange constitute the mechanism of removal of As(V) using FAC. The kinetics of the process is described by a pseudo-second order model.